PERANCANGAN ERP (ENTERPRISE RESOURCE PLANNING) UNTUK PENDIDIKAN TINGGI BERBASIS CRM (CUSTOMER RELATIONSHIP MANAGEMENT) - Anief Rufiyanto (Prosiding SNST Fakultas Teknik, 2011)
The development of ERP (Enterprise Resource Planning) is a software in order to accommodate the resource needs in an educational institution. Both the human resources (human resources) as well as physical resources (material resources) and non-physical (immaterial resources), where can raised projection of the institution in a specified period. Managerial decision making on this subject-based CRM (Customer Relationship Management) that accommodates input from students, alumni and other stakeholders. The system assesses the development of the utilization of existing resources in an educational institution. Because after all educational institutions should have policies not only make a profit as an economic enterprise. Implemented starting from the data of teachers, students, subject matter to, evaluation of students' learning, including the annual report. Will also be known in general satisfaction level and needs during the teaching process takes place. Design and implementation of system 3 components, namely: People (human resources and student), Process (interaction of the learning process and the system) and product (learning content, output), until now there is no a comprehensive model as a tool for evaluating the implementation of resource planning. Keyword: education, Enterprise Resource Planning, managerial, Customer relationship Management,